Motivation Conditions in a Foreign Language Reading Comprehension Course Offering Both a Web-Based Modality and a Face-to-Face Modality - Sergio Lopera Medina (Universidad Nacional de Colombia, 2014)
Motivation plays an important in role in education. Based on the ten macro-strategies proposed by Dörnyei and Csizér (1998), this article analyzes the motivation conditions in a foreign language reading comprehension course using both a web-based modality and a face-to-face modality. A case study was implemented as the primary research method, and five instruments were used to gather data: observations, a teacher's diary, focus groups, questionnaires, and in-depth interviews. The use of teaching aids, mastery gains in reading, proper presentation of tasks, and lack of humor were among the similarities found in the courses. In contrast, constant motivation, technical support, interactions among students, anxiety, and a high number of exercises constituted some of the differences between the modalities.